Cultural Sensitivity in Interventions Aiming to Reduce or Prevent Intimate Partner Violence During Pregnancy: A Scoping Review. (January 2023) - Henriksen, Lena; Kisa, Sezer; Lukasse, Mirjam; Flaathen, Eva Marie; Mortensen, Berit; Karlsen, Elisabeth; Garnweidner-Holme, Lisa
Intimate partner violence (IPV) around the time of pregnancy is a recognized global health problem. Ethnic minorities and immigrant pregnant women experiencing IPV require culturally responsive health services. The aim of this scoping review was to identify aspects of cultural sensitivity in interventions to prevent or reduce IPV among ethnic minorities and immigrant pregnant women in high-income countries. Eight databases were searched in November 2019. Any type of scientific research, quantitative, qualitative, or mixed methods studies regarding interventions against IPV among pregnant women were considered for inclusion. Resnicow et al.'s definition of cultural sensitivity was used to identify aspects of cultural sensitivity. Ten papers relating to nine interventions/studies met our inclusion criteria. These studies, which included randomized controlled trials, a mixed methods study, a program evaluation, and a longitudinal study, were conducted in Australia, Belgium, Norway, and the United States. Aspects of surface cultural sensitivity, including the translation of intervention content into the language of the target group(s) and the involvement of bilingual staff to recruit participants, were identified in eight studies. Deep structure aspects of cultural sensitivity were identified in one study, where the intervention content was pretested among the target group(s). Results that could be related to the culture-sensitive adaptions included successful recruitment of the target population. Three studies were planning to investigate women's experiences of interventions, but no publications were yet available. This scoping review provides evidence that culturally sensitive interventions to reduce or prevent IPV among immigrant pregnant women are limited in number and detail.